PENGEMBANGAN MODUL DIGITAL BERBASIS APLIKASI ANDORID MATERI UNGGAS (POULTRY) BAGI SISWA SMK KULINER FASE E - Aisyah Nurul Firdaus; Lucia Tri Pangesthi; Andika Kuncoro Widagdo; Hidayatun Muyasyaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the Merdeka Curriculum emphasizes student-centered learning, independent learning, the use of technology, and alignment with industry needs. This has encouraged the development of innovative teaching materials, particularly in vocational high schools (SMKs). One such innovation is an Android-based digital module for Poultry learning materials. This study aimed to develop the module, evaluate its material and media feasibility, and examine students' responses to the developed product. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the development stage. The product was validated by three material experts and three media experts, while a limited trial was conducted with 30 tenth-grade Phase E students at SMK Negeri 1 Buduran. Data were collected through validation questionnaires and student response questionnaires, then analyzed descriptively using percentage techniques. The results showed that the Android-based digital module achieved a material feasibility score of 99% and a media feasibility score of 98%, both categorized as highly feasible. In addition, students' responses reached 85%, indicating a very good level of acceptance. These findings suggest that the developed Android-based digital module is highly suitable for use as a teaching material to support Poultry learning in Culinary Vocational High Schools.